ANALISIS PENGARUH CITRA MEREK , KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN - Krisnawati, Silla; Andayani, Sri; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2018)
This study aims to analyze influence the variable of brand image, service quality and price to the variable of customer loyalty in a partial, simultaneous and variables that dominate it. The method of analysis used is multiple linear regression.Population in this research is consumers who use the services of lasika production . The sample used in this study as much 100 respondents drawn from customers of the Event Organizer which works together with Lasika Production by purposive sampling. The results of the research found that Brand Image has positive and significant effect on customer loyalty is partially acceptable. Service quality has positive and significant effect to customer loyalty partially. The price has positive and significant effect to customer loyalty partially. Brand image, service Quality and Price simultaneously significant positive effect on customer loyalty. The factors that most dominating customer loyalty are brand image Keywords: brand image, service quality, prices, customer loyalty